2014
DOI: 10.3138/jcs.48.3.49
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Positive Rights: Access to Health Care and the Canadian Charter of Rights and Freedoms

Abstract: An important debate implicating rights and Canadian social policy concerns whether the Charter of Rights and Freedoms should largely be limited to protecting negative rights, which prevent interference from government, or whether it should include positive rights, which require governments to provide entitlements to social services like health care, housing, or some minimum standard of welfare. After examining the Supreme Court of Canada’s approach to social rights under the Charter, this essay critically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Positive rights are distinguished from negative rights that aim to eliminate government interference with rights (Macfarlane, 2014). Generally, the courts are apprehensive of mandating entitlements to new benefits through section 15(1) because doing so is seen to encroach on the responsibilities of elected branches of government to fulfill their Charter obligations.…”
Section: Positive Rights For Deaf Childrenmentioning
confidence: 99%
“…Positive rights are distinguished from negative rights that aim to eliminate government interference with rights (Macfarlane, 2014). Generally, the courts are apprehensive of mandating entitlements to new benefits through section 15(1) because doing so is seen to encroach on the responsibilities of elected branches of government to fulfill their Charter obligations.…”
Section: Positive Rights For Deaf Childrenmentioning
confidence: 99%
“…In addition, obviously the availability of good palliative care provided by medical power will have an impact on the individual’s decision (if well informed) to avail him/herself of MAID. At the same time, in Canada Charter claims have generally been unsuccessful insofar as they have required the expenditure of state resources not available to the general public (MacFarlane, 2014). This suggests that while the Charter might give suffering individuals a negative right to opt for MAID, it will not serve them well if they seek a positive right to more palliative care options—options that may well have an effect on their decision of whether or not life is worth living.…”
Section: Carter V Canada (Attorney General)mentioning
confidence: 99%
“…In fact, as shown in the preceding section regarding the Eldridge case, section 14 of the Charter, and related jurisprudence, for deaf adults many Charter rights are fulfilled only by sign language accommodations. Extending this argument to young deaf children's right to sign language may depend on the courts reading positive rights into section 15(1) and providing new entitlements to social services (Macfarlane, 2014). In effect, this means that governmental entities must provide ASL and LSQ programming and instruction for all young deaf children and their families.…”
Section: Positive Rights For Deaf Childrenmentioning
confidence: 99%
“…Quebec case of 2005 shows that they have not completely ruled out the possibility of reading positive rights into section 7. In this case, which involved a challenge of a Quebec law that excluded citizens under the age of 30 from full social security benefits, the decision was not unanimous and the judges split three ways on this issue (Macfarlane, 2014). In her ruling, Chief Justice Beverley McLachlin suggested that Snoddon & Paul, "Deaf Children's Right to Sign Language" CJDS 6.1 (March 2017) 13 the meaning of section 7 "should be allowed to develop incrementally" (par.…”
Section: Positive Rights and Sectionmentioning
confidence: 99%
See 1 more Smart Citation